Video encryption using computation between H.264/AVC and AES encryption algorithm - Omar zakaria, Mohamed Abomhara; Khalifa, Othman Omran (IIUM Press, 2011)
With the advanced development of the Internet and multimedia, it is easier for digital data owners to transfer multimedia documents across the Internet. Therefore, multimedia security has become one of the most aspects of communications with the continuous increase in the use online transmission. Some applications, such as TV broadcast and military applications require a special and reliable secure storage or transmission to be completely secured against theft, alteration or misuse. Furthermore, videoconferencing has become a daily characteristic of financial businesses. As it saves time, effort, and travel expenses for large companies. In such applications, digital video is compressed to a low bit rate while it is stored or transmitted [1]. There are several important standards such as MPEG-l, MPEG-2/h.262 and MPEG-4 have been developed for video compression, but with the target to double the coding efficiency and high reliability in video transmission. The Moving Picture Expert Group (MPEG) and the Video Coding Expert Group (VCEG) have developed a new standard that promises to outperform the earlier MPEG-4 and H.263 standard. H.244/AVC provides the most current balance between the coding efficiency, implementation complexity and cost